Futures contract rates as monetary policy forecasts - Giuseppe Ferrero; Andrea Nobili (European Central Bank (ECB), 2008)
The prices of futures contracts on short-term interest rates are commonly used by central banks to gauge market expectations concerning monetary policy decisions. Excess returns - the difference between futures rates and the realized rates - are positive, on average, and statistically significant, both in the euro area and in the United States. We find that these biases are significantly related to the business cycle only in the United States. Moreover, the sign and the significance of the estimated relationships with business cycle indicators are unstable over time. Breaking the excess returns down into risk premium and forecast error components, we find that risk premia are counter-cyclical in both areas. On the contrary, ex-post prediction errors, which represent the greater part of excess returns at longer horizons in both areas, are negatively correlated with the business cycle only in the United States.
Keywords: E43; E44; E52; 330; business cycle; excess returns; futures contracts; monetary policy expectations; Geldpolitik; Frühindikator; Zinsderivat; Eurozone; Großbritannien; Deutschland; EU-Staaten